Pengaruh Gaya Hidup dan Media Sosial terhadap Perilaku Konsumtif Generasi Z di Kota Medan dengan Literasi Keuangan sebagai Media Intervening - Asrun, Nicky Armayfa; Gunawan, Ade (Jurnal Manajemen Bisnis dan Keuangan, 2024)
This research aims to explore how lifestyle choices and social media engagement shape consumer behavior and consider the role of financial literacy in moderating these impacts both directly and indirectly. Using an explanatory quantitative approach, this research focuses on Medan's entire urban generation Z population. Using the Lemeshow formula, the research sample size was determined to be a minimum of 384 respondents. Data analysis follows a three-stage process with SmartPLS, using the PLS-SEM method, outer model analysis, inner model analysis, and hypothesis testing. The research results show that lifestyle, use of social media, and level of financial literacy among generation Z in Medan directly influence their purchasing decisions. Additionally, financial literacy is a mediator, reducing the impact of social media and lifestyle factors on consumer behavior.